A new computational method for the assessment of the passive fire protection applied to a composite containership. (1st July 2023) - Pacheco-Blazquez, R.; Di Capua, D.; García-Espinosa, J.; Casals, O.; Hakkarainen, T.; Tissari, A.; Korkealaakso, A.
Abstract: The current paradigm in ship design is focused in producing ships that are more environmental friendly. Lightweight or advanced materials are the perfect candidate to make ship transportation more efficient, however the current state-of-the-art is in demand of novel techniques that aid in the design of marine composite structures when exposed to fire. This paper aims to describe a technique that couples a fire dynamic simulator with a thermo-mechanical tool specialised in the calculus of laminated FRP structures, the application can be extended to other areas of engineering as well. An application of the technique is illustrated in the analysis of one of the decks of the superstructure of a Panamax containership where a fire has ignited and the active fire protection system is disabled. A second objective addressed in this paper is the discussion of the misconception that composites, although outperforming steel in several mechanical aspects, show a substantial lower thermo-mechanical performance. The research conducted here shows that composite are advantageous from the thermal point of view, and certainly have benefits in their thermo-structural response, specially when the life of human beings is under consideration. Highlights: Fire dynamics simulation of composite structures. Thermo-mechanical analysis of composite structures. Coupling between fire dynamics simulation and thermo-mechanical analysis.